(NmAGNETIKI SO SLOVNYMI OBMENNYMI WZAIMODEJSTWIQMI (B/s - (NnAGAEW(B, (N|DUARD lEONOWI^s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1988)
(NbIBLIOGR(B.: (NS(B. 223-230 (316 (NNAZW(B.)s
Keywords: (N|LEKTRI^ESTWOs